PECULIARITIES OF THE INFLUENCE OF MULTIMORBID PATHOLOGY AND THEIR TREATMENT ON THE DENTAL STATUS (LITERARY REVIEW) (World Bulletin of Public Health, 2022)
Recently, there has been a growing concern among dentists about comorbidities in patients seeking dental care, as this figure, according to some authors, reaches 60-80%. Studies by I.S. Valias et al. (2016) showed that at the dental appointment associated pathology, such as, arterial hypertension occurs in (52%)people, diabetes (31.3%) and cardiovascular disease (27.5%) people.
Keywords: Multimorbid Pathology; Dental Status